INVESTIGATING CUSTOMER PREFERENCE WHEN CHOOSING A RESTAURANT IN SURABAYA, INDONESIA - Alvionita Chrisanti Agustono (Jurnal Hospitality dan Manajemen Jasa, 2017)
Abstract – Investigating Customer Preference When Choosing a Restaurant in Surabaya, IndonesiaThe purpose of the research is to analyses the factors which influencing customers when choosing restaurants in Surabaya, Indonesia. The examination started by doing the secondary research by the author in-depth about the consumer behavior, customers’ preferences, and restaurants industry specifically in Surabaya, Indonesia. The next part of the research is the secondary research which is conducted between 25th December 2016 and 8th January 2017 distributed 200 questionnaires to customers in Surabaya, Indonesia. The result is analyzed and compared to the theoretical background and the literature review. After analyzed and compared the author concluded the result of the factors which influencing customers when choosing restaurant in Surabaya, Indonesia. However, customers in Surabaya, Indonesia influenced by many things when choosing restaurants and the main factors is the quality of the food as the first and the service quality as the second. In addition there are some differences of the influencing factors between female and male when choosing restaurants in Surabaya, Indonesia.